Electric motors DC motors - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
This interactive training unit is designed to familiarize trainees with the basic operation and maintenance of DC motors. After completing this unit, trainees should be able to describe the operation and basic parts of a DC motor. They should also be able to describe basic procedures for maintaining and overhauling a DC motor.
Keywords: Electric motors; Electric controllers